PENGARUH PENGUNGKAPAN ASPEK EKONOMI DAN STRUKTUR MODAL TERHADAP KINERJA PERUSAHAAN (Studi Pada Perusahaan Pertambangan dan Manufaktur yang Terdaftar di BEI Tahun 2015-2016) - SHADRINA, ALYSSA ALMAS (Jurnal Ilmiah Mahasiswa FEB, 2017)
The  purpose  of  this  research  is  to  examine  the  effect  of  economic  aspect disclosure  and  capital  structure  on  company  performance.  Economic  aspect disclosure  is  measured  using  Sustainability  Report  Disclosure  Index  (SRDI)  and capital  structure  is  measured  using  Debt  to  Asset  Ratio  (DAR).  Company performance is measured using Return On Asset (ROA), and firm size is used as the  control  variable.  The  population  of  this  research  is  companies  listed  in  the Indonesia  Stock  Exchange  (IDX)  in  the  period  of  2015-2016.  Using  purposive sampling method, 21 companies are selected as the research sample. The result of multiple  linear  regression  analysis  show  that  economic  aspect  disclosure  and capital structure have positive effects on company performance. Keywords: economic aspect disclosure, capital structure, company  performance, firm size